Pharmaceutical study on certain selective serotonin reuptake inhibitor - Shahinaze Amry Aly Fouad; Emad B. Basalious; Mohamed Ahmed Elnabarawi; Saadia Ahmed Tayel (Cairo : Shahinaze Amry Aly Fouad, 2016)
Dapoxetine, as dapoxetine hydrochloride (D), is the first and only selective serotonin reuptake inhibitor licensed for the treatment of PE in men. However, oral D suffers from extensive first pass metabolism, resulting in poor bioavailability (42%). Therefore, transmucosal systems of D were designed in an attempt to increase its bioavailability. In chapter (I), a 2.3 full factorial design was employed to study the effect of different formulation variables. An optimized formulation was prepared and evaluated. It showed a rapid permeation compared to the drug suspension. In chapter (II), nanocarrier systems for transmucosal delivery of D were prepared. In chapter (III), Part (I) and (II) involved determination of the pharmacokinetics of D after sublingual and intranasal delivery from ISTM compared to the oral market product (priligy® 30 mg, tablets) and after the intranasal delivery of D from IDNP of the optimized formulation compared to the oral D-loaded nanocarrier formulation
Thesis (Ph.D.) - Cairo University - Faculty of Pharmacy - Department of Pharmaceutics
Issued also as CD
Keywords: Dapoxetine hydrochloride; Lyophilized matrices; Selective serotonin reuptake inhibitor